Cygnus: a psychoeducational group for carers of people with a personality disorder. (1st May 2020) - Sutherland, Ruth; Holland, Alice; Prince, Sharon
Abstract : National Institute for Health and Care Excellence guidance suggests that carers of individuals with a diagnosis of borderline personality disorder experience high levels of psychological distress, yet few services in the UK offer specific support to this group of carers. This article will describe the development of a psychoeducational carers' group based on schema theory (Young et al, 2003), including the development of the role of carer experts-by-experience as group co-facilitators. Initial outcome data from the pilot suggest that carers are highly satisfied with the group and that it improves their knowledge, understanding and personal well-being.